Use of biochar and coal ash as passive sorbent barriers for long-term mitigation of chlorinated solvent vapours - Settimi, Clarissa; Conti, Benedetta; Verginelli, Iason; Zingaretti, Daniela; Bortone, Immacolata; Coulon, Frederic; Baciocchi, Renato (Elsevier, 2025)
This study explores the potential of biochar and coal ashes as novel passive sorbent barriers to mitigate chlorinated solvent vapours at contaminated sites, addressing the need for sustainable risk mitigation alternatives to traditional remediation. Trichloroethylene (TCE) was used as a model compound in adsorption batch tests under varying temperatures (5–35 °C) and humidity levels (0–50 %) to evaluate the adsorption capacity of biochar derived from pyrolysed biomass and coal ash from wood pellets gasification. All materials exhibited good adsorption capacities (75–170 mg g^−1), with biochar outperforming coal ashes due to higher carbon content. Adsorption capacity showed a decline with increasing temperature and humidity of maximum 30 %, consistent with exothermic physical adsorption. Freundlich isotherms best described the adsorption behaviour, suggesting a non-linear, reversible, and multilayer process. Column adsorption tests of TCE vapours were then carried out with biochar to assess the adsorption behaviour under dynamic conditions showing good performance. Modelling revealed that a 50 cm thick barrier of biochar could effectively mitigate chlorinated vapours for over 15 years for entering concentrations up to 1 g m^−3, proving the suitability of the tested materials as long-term risk management solutions in the subsurface. The overall results challenge the prevailing reliance on traditional remediation systems, highlighting the potential of a passive risk mitigation approach aligned with sustainability objectives and advancing knowledge in this field.
Keywords: 4104 Environmental Management; 4105 Pollution and Contamination; Environmental Sciences; Biochar; Chlorinated VOCs; Adsorption; Contaminated sites; Risk management strategies